Attenuation in Rectangular Waveguides with Finite Conductivity Walls - Yeap, K; Tham, C; Yassin, G; Yeong, K (2011)
We present a fundamental and accurate approach to compute the attenuation of electromagnetic waves propagating in rectangular waveguides with finite conductivity walls. The wavenumbers kx and ky in the x and y directions respectively, are obtained as roots of a set of transcendental equations derived by matching the tangential component of the electric field (E) and the magnetic field (H) at the surface of the waveguide walls. The electrical properties of the wall material are determined by the complex permittivity ε, permeability μ, and conductivity σ. We have examined the validity of our model by carrying out measurements on the loss arising from the fundamental TE10 mode near the cutoff frequency. We also found good agreement between our results and those obtained by others including Papadopoulos' perturbation method across a wide range of frequencies, in particular in the vicinity of cutoff. In the presence of degenerate modes however, our method gives higher losses, which we attribute to the coupling between modes as a result of dispersion.